EVALUASI PROGRAM PELATIHAN KEWIRFAUSAHAAN MODUL START and IMPROVE YOUR BUSINESS (SIYB) PADA INSTITUT PEMBINAAN DAN PENGEMBANGAN KEWIRAUSAHAAN TIMOR-LESTE - Sergio J. da C. Pereira (REFORMASI, 2015)
This research is motivated by the need to foster the emergence of SMEs in Timor-Leste since the role of SMEs may be able to provide jobs and contribute to an increase in tax revenue. there are two problems in the study: (1) How CIPP model evaluation training program implemented by IADE, (2) the challenges of program implementation SIYB entrepreneurship training modules what are faced by IADE. Research on the evaluation of SME entrepreneurship training program aims to describe the extent to which the results of the evaluation of the CIPP model of entrepreneurship training programs (2) To know the challenges of entrepreneurship training programs. The method used is descriptive qualitative research focus is to use the model Context, Input, Process, and Product (CIPP) and data collection techniques are interviews, documentation and observation in depth. Analysis of the data used interactive model (Saldana Miles and Huberman, 2014). Its findings are (Input) assistance is still lacking. Lack of monitoring and evaluation. Process (process) Addition of experience and practical knowledge and suitable materials, the need for exercises (exercise) It should be good for TNA. (Product) the addition of knowledge and experience, expansion of business units, increased revenues, and increase the amount of labor.